2021
DOI: 10.1186/s40779-021-00313-8
|View full text |Cite
|
Sign up to set email alerts
|

Military medical research on internal diseases in modern warfare: new concepts, demands, challenges, and opportunities

Abstract: Battlefield internal medicine aims at the treatment of combatants and noncombatants with various internal diseases on the battlefield. The military medical research on battlefield internal diseases focuses on the pathogenesis, clinical management, and prevention of internal diseases under military war conditions. In both wartime and peacetime, the soldiers suffer from more internal diseases than surgical wounds. With the introduction of high-tech weapons, including chemical, physical, and biological agents, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…According to annual statistics from the United States Naval Medical Service, during World War I, gastrointestinal diseases were the third most common diseases that led to American navy servicemen's medical admissions. In World War II, both the American army and navy had a large number of hospital admissions for digestive disorders which were the third most common in the medical diseases [1][2][3] .Digestive diseases were the fourth most common medical disease that caused American navy's hospital admissions during the Korean War.And gastrointestinal diseases were again the third most common diseases that led to American navy servicemen's medical admissions during the Vietnam War.Judging from disease attrition of Chinese army in previous wars,the incidence of the digestive system diseases was also very high, which took the rst place in the War of Resistance Against Japanese Aggression and in the National War of Liberation, and took the second place in the War of Resistance Against American Aggression and Aid Korea and in Sino-Vitnamese War.In recent years, relevant investigations and studies have shown that the incidence of digestive system diseases of soldiers is still quite high in all medical diseases, of which, functional bowel disease and gastrointestinal ulcer are more common during the training period, and the risk of functional bowel disease may increase with the extension of military service time [4][5] .The digestive system is closely related to the nervous system and is sensitive to changes of the external environment. Due to living in a relatively closed and depressing space, and receiving intense physical training,the army servicemen often have great psychological pressure.Therefore, army servicemen are prone to digestive diseases,which can further aggravate their psychological burden, reduce the quality of life, and even seriously affect combat capacity [6] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to annual statistics from the United States Naval Medical Service, during World War I, gastrointestinal diseases were the third most common diseases that led to American navy servicemen's medical admissions. In World War II, both the American army and navy had a large number of hospital admissions for digestive disorders which were the third most common in the medical diseases [1][2][3] .Digestive diseases were the fourth most common medical disease that caused American navy's hospital admissions during the Korean War.And gastrointestinal diseases were again the third most common diseases that led to American navy servicemen's medical admissions during the Vietnam War.Judging from disease attrition of Chinese army in previous wars,the incidence of the digestive system diseases was also very high, which took the rst place in the War of Resistance Against Japanese Aggression and in the National War of Liberation, and took the second place in the War of Resistance Against American Aggression and Aid Korea and in Sino-Vitnamese War.In recent years, relevant investigations and studies have shown that the incidence of digestive system diseases of soldiers is still quite high in all medical diseases, of which, functional bowel disease and gastrointestinal ulcer are more common during the training period, and the risk of functional bowel disease may increase with the extension of military service time [4][5] .The digestive system is closely related to the nervous system and is sensitive to changes of the external environment. Due to living in a relatively closed and depressing space, and receiving intense physical training,the army servicemen often have great psychological pressure.Therefore, army servicemen are prone to digestive diseases,which can further aggravate their psychological burden, reduce the quality of life, and even seriously affect combat capacity [6] .…”
Section: Discussionmentioning
confidence: 99%
“…And the contents of this questionnaire include ve aspects: (1)Basic information: Gender, age, height, weight, educational background, military services, military service time, status, smoking, diet habits, family history of digestive diseases and use history of NSAIDs(aspirin, clopidogrel, ibuprofen,etc. ); (2)Training and education: the daily military training time, education on digestive disease prevention knowledge; (3)digestive diseases: acute gastroenteritis, digestive ulcer, gastrointestinal bleeding, in ammatory bowel disease, functional bowel disease, gastroesophageal re ux disease, pancreatitis, abnormal liver function nausea;(4)Related symptoms: vomiting, abdominal distension, diarrhea, abdominal pain, constipation, poor appetite, acid re ux;(5)Treatment: medical institutions, examination items, treatment effect, etc.…”
Section: Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, laser dazzling technology has wide application prospects in the public security field. Laser dazzling devices can cause temporary vision loss of the target without causing physical damage, which has become an important direction in the current research of high-tech nonlethal laser antiterrorism devices [3], laser radar or illuminations of car drivers [4][5][6][7]. At present, there are some reports about the development of laser dazzling devices and car driver illumination, but no specific parameters are involved.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, military medicine is essential, given the increase of military conflicts worldwide. To better guarantee the success of modern warfare and increase the troops' combat effectiveness more scientifically, strengthening the development of military medical research on battlefield internal medicine is an imperative military medical task (Liu et al, 2021). Also, there are several issues regarding women combatants and women in the military serving in theaters of war that need deliberation.…”
Section: Introductionmentioning
confidence: 99%